EFL TEACHERS’ AND LEARNERS’ PERCEPTION OF NEGOTIATED SYLLABUS: AN EFFECTIVE WAY OF IMPROVING SPEAKING ABILITY - Amrang, Amrang; An Nur, Muh. Jabal (English Language Teaching for EFL Learners Journal, 2021)
The appropriateness of learning material for learners’ interests and professions is highly important. The more relevant learning materials and learners’ interests, the easier it is for them to participate in a conversation. This research aimed to investigate the EFL teachers’ and learners’ perception of the negotiated syllabus and the improvement of learners’ English speaking ability. This research employed a descriptive qualitative research method in which data collected through documents and in-depth interviews. The subject of this research consisted of five EFL teachers and ten EFL learners. The qualitative results showed both teachers and learners giving positive responses in learning speaking English through the negotiated syllabus. In addition to learners’ responses, the negotiated syllabus has facilitated the learners in improving their English speaking ability to be taught based on their needs and wants. On the other hand, vocabulary and comprehension, the speaking skills elements, were improved more than other speaking skill elements.